Intellectual Property Rights: Institutional Approach - S. P. Rogozhin; S. L. Sazanova (Управление)
The authors consider the intellectual property rights from two points of view: legal theory and institutional economical theory. Contents of “intellectual property” and “intellectual rights” concepts have been revealed in this paper, and the necessity of their study has been justified not only from the legal point of view, but also from the economic one. The authors emphasize that the institutional economics in general and the economic theory of property rights, in particular, have a great potential in the study both of theoretical and practical aspects related to intellectual rights. According to the authors, it is the institutional approach which will create an effective legislation in this area.